2009
DOI: 10.1088/0031-8949/81/01/015301
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of M-shell x-ray transitions in Zn-like through Co-like W

Abstract: The M-shell x-ray emission of highly charged tungsten ions has been investigated at the Livermore electron beam ion trap facility. Using the SuperEBIT electron beam ion trap and a NASA x-ray calorimeter array, transitions connecting to levels of the ground configurations in the 1500–3600 eV spectral range of zinc-like W44+ through cobalt-like W47+ have been measured. The measured spectra are compared with theoretical line positions and emissivities calculated using the FAC code.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
105
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(121 citation statements)
references
References 41 publications
13
105
0
3
Order By: Relevance
“…Therefore, a significant amount of theoretical [25,27,[44][45][46] and experimental [14,[17][18][19][20]22] work has been performed on M-shell spectra of various ion charge species of tungsten. In this context, Clementson et al [18] have measured the M-shell spectra of Zn-like W 44+ through…”
Section: Excitation Of Co-like Through Zn-like Tungsten Ionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a significant amount of theoretical [25,27,[44][45][46] and experimental [14,[17][18][19][20]22] work has been performed on M-shell spectra of various ion charge species of tungsten. In this context, Clementson et al [18] have measured the M-shell spectra of Zn-like W 44+ through…”
Section: Excitation Of Co-like Through Zn-like Tungsten Ionsmentioning
confidence: 99%
“…They studied spectra at excitation energies 3.3, 4.0 and 4.1 keV and observed strong line emission in the 1500-3600 eV soft X-ray range. Clementson et al [18] also utilized FAC code to carry out relativistic atomic structure and collisional-radiative calculations and compared their calculated and observed spectra. For the electron impact excitation studies of these ions, Zhang et al [44,45] reported their relativistic distorted wave collision strengths for Ni-like and Cu-like tungsten ions.…”
Section: Excitation Of Co-like Through Zn-like Tungsten Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurements performed on soft X-ray (SXR) radiations originating from the magnetic fusion plasmas are a standard way to obtain valuable information about the transport of particles in the reactor volume, density, and magnetic confi guration [1][2][3][4][5]. Attention focused on tungsten material is associated with the fact that it became a leading candidate for the plasma-facing material in the future International Thermonuclear Experimental Reactor (ITER) and future tokamaks.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the modelling of the soft L, M, and N X-ray spectra structures for tungsten in high--temperature tokamak plasmas has been performed within the framework of collisional-radiative (CR) model using the fl exible atomic code (FAC) package [4,5,9,10] for electron temperatures and densities relevant to WEST tokamak.…”
Section: Introductionmentioning
confidence: 99%